2020
DOI: 10.5121/sipij.2020.11104
|View full text |Cite
|
Sign up to set email alerts
|

Suitable Mother Wavelet Selection for EEG Signals Analysis: Frequency Bands Decomposition and Discriminative Feature Selection

Abstract: Wavelet transform (WT) is a powerful modern tool for time-frequency analysis of non-stationary signals such as electroencephalogram (EEG). The aim of this study is to choose the best and suitable mother wavelet function (MWT) for analyzing normal, seizure-free and seizured EEG signals. Several MWTs can be used, but the best MWT is the one that conserves the quasi-totality of information of the original signal on wavelet coefficients and gather more EEG rhythms in terms of frequency. In this study, Daubechies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…On the other hand, the work in Ref. [22] found that db4 is the most suitable MW for EEG frequency band decomposition using linear discriminant analysis (LDA) for feature selection. The pipeline of the proposed system is shown in Figure 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, the work in Ref. [22] found that db4 is the most suitable MW for EEG frequency band decomposition using linear discriminant analysis (LDA) for feature selection. The pipeline of the proposed system is shown in Figure 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…N. Ji et al [37] found that time-error minimization and F1-score maximization can offer the relevant wavelet selection for gait event detection. R. Atangana et al [38] proposed the selection metrics based on the percentage root mean square difference (PRD), the SNR, and the simulated frequencies to find the best and suitable wavelet for assessing normal, seizure-free, and EEG signals showing seizures.…”
Section: Introductionmentioning
confidence: 99%